Effects of lactic acid bacteria isolated from dairy products on lipid pattern of rats fed with a high fat diet - Sahar Fouladi; Elham Moazamian (Iranian Journal of Microbiology)
Background and Objectives: A unique characteristic of probiotics is obesity and fatty liver control. In this study, the effect of lactic-acid-bacteria (LABs) isolated from dairy products was investigated on weight changes, blood biochemical indexes and liver tissue in mice fed a high-fat diet. Materials and Methods: A total of 49 rats were assigned to 7 groups. The LAB-treated groups received the high-cholesterol diet supplemented with Lactobacillus reuteri, Lactobacillus plantarum, and Bifidobacterium animalis isolated from yogurt. At the end of 4 weeks, body weight changes, lipid factors and liver enzymes as well as liver lipid deposition and adipocyte size were measured. Results: Serum low-density lipoprotein, total cholesterol, triglyceride levels and hepatic lipid deposition were significantly decreased in rats treated with LABs. The maximum and minimum weights were observed in the first and fourth weeks after treating with Lactobacillus and Bifidobacterium isolates, respectively. Liver enzymes were significantly decreased by LABs, especially in the group receiving concomitant administration of Lactobacillus and Bifidobacterium. Fatty liver process was reduced in the fat-fed group treated with L. reuteri. Conclusion: LABs caused decreases in body weight gain, liver function, and adipocyte size. Therefore, coadministration of Lactobacillus and Bifidobacterium in dairy products can significantly decrease lipid profile.